Accreditation of prior experiential learning and democratisation of education: empirical evidence using multiple regression analysis - Afzhan Khan Mohamad Khalil; Widad Othman; Nurul Amanina Muhamad Jufari; Aznan Ariffin (2019)
Access to education is still a worldwide problem due to various inequalities. The Malaysian Qualifications Agency (MQA) introduced the Accreditation of Prior Experiential Learning (APEL) mechanism which enables individuals who have work experience but lack in formal academic qualifications to pursue their studies at higher educational institutions. APEL Centre is an approved assessment centre for MQA. The main purpose of this study is to examine the relationship between service quality provided by APEL Centre, awareness on APEL and democratisation of education. A literature review to build the research instrument. Survey questionnaires were administered and a total of 168 were usable responses from Open University Malaysia (OUM). Face-to-face data collection procedure was adopted. A total of 63% of the respondents were aware of the entry requirements using APEL whereas 27% needed more clarification. The candidates who obtained the services from APEL Centre were interested to gain admission in Diploma (3%), Degree (58%) and Master (39%) programmes in Malaysia. The data collected were cleaned and issues related to data normality (Kurtosis < 3.00; Skewness < 1.00) were primarily resolved. The Cronbach Alpha for service quality of APEL Centre (a = 0.97), awareness on APEL (a = 0.94) and democratisation of education (a = 0.96) were far above acceptable. The reported R square (0.54) indicated goodness of fit of the total regression model. Service quality provided by APEL Centre (p = 0.01) and awareness on APEL (p = 0.02) were both significant variables when examined against democratisation of education in OUM. The empirical evidence given clearly implies that APEL can help increase access to education. The role of informal and non-formal education can heighten global citizenship of the candidates. Future researchers are recommended to validate the existing measurement by performing confirmatory factor analysis and qualitative interviews to narrow the methodological gap available. (Abstract by authors)